2019
DOI: 10.1289/ehp5165
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Phthalates and Neurodevelopment in the CHAMACOS Cohort

Abstract: Background:Previous studies suggest that prenatal exposure to phthalates, ubiquitous synthetic chemicals, may adversely affect neurodevelopment. However, data are limited on how phthalates affect cognition, executive function, and behavioral function into adolescence.Objective:We aimed to investigate associations of prenatal phthalate exposure with neurodevelopment in childhood and adolescence in the Center for the Health Assessment of Mothers and Children of Salinas (CHAMACOS) study.Methods:We examined associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 63 publications
(94 reference statements)
2
29
2
1
Order By: Relevance
“…Concentrations measured in pregnant women from Korea, China, Taiwan, and the United States were, in general, somewhat higher ( Factor-Litvak et al. 2014 ; Hyland et al. 2019 ; JI Kim et al.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Concentrations measured in pregnant women from Korea, China, Taiwan, and the United States were, in general, somewhat higher ( Factor-Litvak et al. 2014 ; Hyland et al. 2019 ; JI Kim et al.…”
Section: Discussionmentioning
confidence: 97%
“…2013 ; Whyatt et al. 2012 ) and IQ ( Hyland et al. 2019 ), but the findings are inconsistent regarding the exact phthalate metabolites, timing of exposure, and the sex-specific effect of the associations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have reported that increased levels of glycerophospholipids were related to liver injury 61 and dementia 62,63 . A previous study reported that exposure to phthalate mixtures or metabolites of phthalates induced abnormal cognitive ability in adult rats 64,65 . So, the increase of glycerophospholipids may be responsible for decreased cognitive flexibility.…”
Section: Discussionmentioning
confidence: 98%
“…Behavior impairments are particularly more prevalent in boys (Q. Zhang et al, 2019). Furthermore, Hyland and colleagues conducted a cohort study in which they evaluated the relationship between maternal urinary phthalate metabolite concentrations and neurodevelopmental outcomes in subjects from age 7 through 16 (Hyland et al, 2019). Despite the fact that most phthalate metabolites showed no association with neurobehavioral patterns, an interesting result is that metabolites of low‐molecular weight phthalates (LMWP) were moderately associated with internalizing and externalizing behaviors in adolescents (Hyland et al, 2019).…”
Section: Introductionmentioning
confidence: 99%